A Decision Support Tool for Urban Freight Transport Planning Based on a Multi-Objective Evolutionary Algorithm - Miguel, Fabio Maximiliano (2019)
Fil: Miguel, Fabio M. Universidad Nacional de Río Negro, Sede Alto Valle y Valle Medio. Villa Regina; Argentina